The Influence of Blended Learning Models on Students' Interest In Learning Citizenship Education In Primary Schools - Apriliansyah, Violyta; Misriandi, Misriandi; Gunadi, Andi Ahmad (Eduvest - Journal of Universal Studies, 2023)
This study aims to determine the effect of the blended learning learning model on students' learning interest in class V SDN Kemayora 15. This type of research is a true experiment with a posttest applied to both classes, namely the experimental class and the control class. The population in this study were all VB and VC grade students at SDN Kemayoran 15 with a total of 52 students. Sampling in this study was carried out by simple random sampling technique. There are two types of instruments used to obtain data, namely distributing questionnaires of student interest in learning and student learning outcomes tests. The data obtained were then analyzed using the Wilcoxon test and the Mann Whitney test. Based on the SPSS results above, it is known that the Asymp. Sig. (2-tailed) of 0.000. So that 0.000 is smaller than 0.05 or 0.000 <0.05. Then the hypothesis is accepted. The results of this study show the influence of the blended learning learning model on students' learning interest in civics learning in elementary schools.